E-sports: Definition and social implications - Marko Marelić; Dino Vukušić (Exercise and Quality of Life)
The development of video games can be traced back to the 80s of the last century. The final phase of the gaming industry’s development brought with it another phenomenon — e-sport. “Electronic sport” presupposes playing video games in a competitive setting, with emphasis on increased “institutionalization” of gaming activity through the organization of e-sports teams and official international competitions. In order to define esports, it’s important to note that not every activity of playing video games can be described as e-sport, but every e-sport is essentially playing video games. The interest for the phenomenon of electronic sport has increased over the past several years in all social sciences, including sociology. This paper aims to present several dimensions of the “electronic sport” phenomenon, review the existing research in this field, compare various aspects of e-sports and “traditional” sports, and discuss the formation of new subcultural group gathered around video games. The key task of this paper is to examine the distance between e-sports and “traditional” sport and frame the socio-economic scale of the phenomenon.